Gender and education inequalities in dynapenia-free life expectancy: ELSI-Brazil - Viviane Santos Borges; Mirela Castro Santos Camargos; Fabíola Bof de Andrade (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE To estimate the dynapenia-free life expectancy among community-dwelling older Brazilian adults and evaluate gender-related and educational differences. METHODS This is a cross-sectional study. The data were obtained from the Estudo Longitudinal da Saúde dos Idosos Brasileiros (ELSI-Brazil - Brazilian Longitudinal Study of Aging), conducted from 2015 to 2016 in Brazil. Dynapenia is defined as low muscle strength (< 27kg for men and < 16kg for women), measured with a handgrip dynamometer. The dynapenia-free life expectancy was estimated using the Sullivan method based on the standard period life table and dynapenia prevalence, stratified by age groups, gender, and schooling. RESULTS A total of 8,827 participants, aged 50 and over (53.3% women), were investigated. The prevalence of dynapenia was 17.7% among men and 18.5% among women. The women live longer and with more years free of dynapenia than men. Those in the higher education category (four or more years) presented an advantage in the dynapenia-free life expectancy estimates. CONCLUSIONS The results of this study suggest the substantial impact of dynapenia on longer dynapenia-free life expectancy among older people. Understanding dynapenia prevalence and dynapenia-free life expectancy could assist in predicting care needs, as well as targeting efforts to delay the onset of complications related to it at older ages. Without the implementation of policy regarding dynapenia prevention, inequalities in health due to gender and socioeconomic status may continue to increase.